Peningkatan Profesionalisme Guru Sekolah Dasar melalui Penerapan Strategi Pembelajaran Aktif Berbasis Teknologi - Lilia Indriani; Rini Estiyowati Ikaningrum; Mey Nur Aini (Universitas Muhammadiyah Semarang, 2026)
Global transformations necessitate paradigm shifts in education, particularly through the integration of technology into teaching and learning. This shift encourages a transition from traditional methods to active learning strategies, presenting both opportunities and challenges for teachers seeking to enhance professional competence. Field observations reveal that the implementation of technology-based active learning remains limited, underscoring the need for deeper pedagogical understanding. The Community Service Program (PKM) conducted in elementary schools in Magelang, Central Java, aimed to strengthen teacher professionalism by developing teaching modules that integrate active learning with technological tools. The program employed three stages: mentoring, modeling, and assessment, using questionnaires administered before and after workshops. Results demonstrated significant improvements in pedagogical competence (96.68%) and professional competence (99.97%), highlighting the effectiveness of revised teaching modules. These outcomes emphasize the importance of integrating active learning strategies with technology to foster sustainable professional growth. Ultimately, the PKM initiative contributes to long-term improvements in instructional quality and enriches students' learning experience.